Premature mortality in India due to PM2.5 and ozone exposure. Issue 9 (14th May 2016) - Ghude, Sachin D.; Chate, D. M.; Jena, C.; Beig, G.; Kumar, R.; Barth, M. C.; Pfister, G. G.; Fadnavis, S.; Pithani, Prakash
Abstract: This bottom‐up modeling study, supported by new population census 2011 data, simulates ozone (O3 ) and fine particulate matter (PM2.5 ) exposure on local to regional scales. It quantifies, present‐day premature mortalities associated with the exposure to near‐surface PM2.5 and O3 concentrations in India using a regional chemistry model. We estimate that PM2.5 exposure leads to about 570, 000 (CI95: 320, 000–730, 000) premature mortalities in 2011. On a national scale, our estimate of mortality by chronic obstructive pulmonary disease (COPD) due to O3 exposure is about 12, 000 people. The Indo‐Gangetic region accounts for a large part ( 42%) of the estimated mortalities. The associated lost life expectancy is calculated as 3.4 ± 1.1 years for all of India with highest values found for Delhi (6.3 ± 2.2 years). The economic cost of estimated premature mortalities associated with PM2.5 and O3 exposure is about 640 (350–800) billion USD in 2011, which is a factor of 10 higher than total expenditure on health by public and private expenditure. Key Points: PM2.5 exposure is causing 570, 000 premature mortalities Economic cost of estimated premature mortalities is about 640 billion USD PM2.5 should be the primary target for reducing pollution impacts on health